t=−3 , find t^2−2t−1

we need to substitute the value of 't' in the equation. we are given the value of 't'. it is equal to 3. Now, substitutting 3 in the place of 't' within the equation gives: 

(3)^2 - 2(3) - 1 

= (3 x 3) - (2 x 3) - 1

= 9 - 6 - 1

= 2

Therefore, when 't' = 3, t^2-2t-1 = 2

Answered by Dhwani P. Economics tutor

6930 Views

See similar Economics GCSE tutors

Related Economics GCSE answers

All answers ▸

What is the main government objectives to maximize economic growth?


Analyse Indifference Curves and the effect on lower prices. (20)


What factors can shift the demand curve in a market?


How can you calculate the Price and Quantity at a market equilibrium given the Demand curve P = 20 - Q and the Supply curve P = 3Q


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences